2018
DOI: 10.1159/000489389
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Phototherapy: A Novel Therapy to Prevent Allergic Skin Disease for At Least 5 Years

Abstract: Background: Preventing the development of allergic skin disease in children is the best way to treat the disease. Objectives: Ultraviolet (UV)-free blue light phototherapy has been reported to treat atopic eczema. We evaluated the effect of neonatal phototherapy on allergic skin disease in children. Methods: We randomly recruited 117,041 children from an insurance research database. Those with neonatal jaundice and receiving neonatal phototherapy were classified as the icteric-phototherapy group (n = 4,744), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…Nineteen studies were in the qualitative synthesis. [10][11][12][13][14][15][25][26][27][28][29][30][31][32][33][34][35][36][37] In the end, fourteen studies reporting the effect estimate were synthesized in the meta-analysis. Our search did not reveal any ongoing and unpublished studies.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Nineteen studies were in the qualitative synthesis. [10][11][12][13][14][15][25][26][27][28][29][30][31][32][33][34][35][36][37] In the end, fourteen studies reporting the effect estimate were synthesized in the meta-analysis. Our search did not reveal any ongoing and unpublished studies.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Our study [2] comprised 4,744 jaundiced infants treated with phototherapy, 5,003 jaundiced infants not treated with phototherapy, and 107,294 anicteric infants. For a study of allergic skin disease, I believe that the sample size is satisfactory.…”
mentioning
confidence: 99%
“…The decreased frequency of clinical visits for allergic skin disease and reduced prescription of topical agents was 38.3% for boys aged 2 years (Table 3) [2] and 64.3% for girls aged 4 years (Table 4) [2], respectively. The large number of subjects and the dramatic decrease in clinical visits and topical agent use suggest that using blue light to prevent allergic skin disease is feasible.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report from a retrospective review of administrative claims data in Taiwan published in Neonatology concluded that “Blue light therapy in newborns may be a novel method to efficiently prevent allergic skin disease for at least 5 years” [1]. The effect size is tiny, the evidence to support this claim is weak, and we are concerned that it could lead to harm to newborns and their families.…”
mentioning
confidence: 99%